Effect of diaminopropionic acid (Dap) on the biophysical properties of a modified synthetic channel-forming peptide - Bukovnik, Urska; Sala-Rabanal, Monica; Francis, Simonne; Frazier, Shawnalea J.; Schultz, Bruce D.; Nichols, Colin G.; Tomich, John M. (My University, 2013)
Channel replacement therapy, based on synthetic channel-forming peptides (CFPs) with the ability to supersede defective endogenous ion channels, is a novel treatment modality that may augment existing interventions against multiple diseases. Previously, we derived CFPs from the second transmembrane segment of the α-subunit of the glycine receptor, M2GlyR, which forms chloride-selective channels in its native form. The best candidate, NK₄-M2GlyR T19R, S22W (p22-T19R, S22W), was water-soluble, incorporated into cell membranes and was nonimmunogenic, but lacked the structural properties for high conductance and anion selectivity when assembled into a pore. Further studies suggested that the threonine residues at positions 13, 17, and 20 line the pore of assembled p22-T19R, S22W, and here we used 2,3-diaminopropionic acid (Dap) substitutions to introduce positive charges to the pore-lining interface of the predicted p22-T19R, S22W channel. Dap-substituted p22-T19R, S22W peptides retained the α-helical secondary structure characteristic of their parent peptide, and induced short-circuit transepithelial currents when exposed to the apical membrane of Madin-Darby canine kidney (MDCK) cells; the sequences containing multiple Dap-substituted residues induced larger currents than the peptides with single or no Dap substitutions. To gain further insights into the effects of Dap residues on the properties of the putative pore, we performed two-electrode voltage clamp electrophysiology on Xenopus oocytes exposed to p22-T19R, S22W or its Dap-modified analogues. We observed that Dap-substituted peptides also induced significantly larger voltage-dependent currents than the parent compound, but there was no apparent change in reversal potential upon replacement of external Na⁺, Cl⁻ or K⁺, indicating that these currents remained nonselective. These results suggest that the introduction of positively charged side chains in predicted pore-lining residues does not improve anion-to-cation selectivity, but results in higher conductance, perhaps due to higher oligomerization numbers.
Citation: Bukovnik, U., Sala-Rabanal, M., Francis, S., Frazier, S. J., Schultz, B. D., Nichols, C. G., & Tomich, J. M. (2013). Effect of diaminopropionic acid (Dap) on the biophysical properties of a modified synthetic achannel-forming peptide. Molecular Pharmaceutics, 10(10), 3959-3966.
Keywords: Channel-forming peptide; Ion selectivity; Anion channel; Chloride channel; Diaminopropionic acid; Dap; Channel replacement therapy; Cystic fibrosis